Analisis Semantik pada Puisi Kangen Karya WS Rendra - Najwa Fasyah; Intan Christine Nainggolan; Novia Marissa Valerina Pardosi; Yati Virma Saragih (Universitas Serambi Mekkah, 2025)
This study analyzes the semantic meaning in the poem